Maxwelleus, a new genus of Curculionidae from the Himalayas, with two new species (Coleoptera: Curculionidae: Molytinae: Euderini) - Meregalli, Massimo (Zootaxa, 2022)
The new genus Maxwelleus, with two new species, M. tibetanus (China, Tibet) and M. birmanus (Myanmar [Burma]), is described and illustrated. The new genus is immediately recognized by large body size (12.5-13.8 mm), pronotum with a distinct transverse groove or constriction behind apex and elytra with narrow but distinct transverse patches of yellow scales. A key to the species is given.